What variability tells us about motor expertise: measurements and perspectives from a complex system approach - Komar, J.; Seifert, L.; Thouvarecq, R. (Movement & Sport Sciences - Science & Motricité, 2015)
In this review, we revisit the concept of movement variability in motor expertise from the perspective of complex systems theory; we do so by defining performers and their relationships with the environment. The complex systems perspective places the focus on the functional role of movement variability as an emergent response to interacting constraints as performers pursue task-goals. We therefore show how the shift in theoretical focus towards the functional role of variability has entailed a reconsideration of the way this key property of motor expertise should be assessed. We then present the main theoretical issues surrounding movement variability and expertise through examples of empirical applications of the relevant tools and concepts in the sport and movement sciences.